Non‐invasive prenatal testing for fetal aneuploidies in the first trimester of pregnancy. (1st December 2014) - Song, Y.; Huang, S.; Zhou, X.; Jiang, Y.; Qi, Q.; Bian, X.; Zhang, J.; Yan, Y.; Cram, D. S.; Liu, J.
ABSTRACT Objectives To evaluate the feasibility of non‐invasive prenatal testing (NIPT) of maternal plasma samples collected from pregnant Chinese women in early gestation, between 8 + 0 and 12 + 6 weeks' gestation. Methods In this pilot study, 212 women with high‐risk pregnancies were recruited at a single Chinese Hospital. Fetal aneuploidies associated with chromosomes 21, 18, 13, X and Y were detected by massively parallel sequencing of maternal plasma DNA samples. Invasive prenatal diagnosis by either chorionic villus sampling or amniocentesis and then karyotyping was offered to all women to confirm both positive and negative NIPT results. Fetal DNA fraction was also determined in male pregnancies, by the relative percentage of Y‐chromosome sequences. All confirmed NIPT‐negative pregnancies were followed up to birth and neonates were clinically evaluated for any symptoms of chromosomal disease. Results Autosomal aneuploidies trisomy 21 (n = 2), 18 (n = 1) and 13 (n = 1) were detected by NIPT and confirmed by amniocentesis and karyotyping. There were one false‐positive 45, X sample and two false‐negative samples associated with fetal karyotypes 47, XXY and 45, X[16]/47, XXX[14]. In the 100 male pregnancies, the median fetal DNA fraction was 8.54% and there was a trend towards an increasing fetal fraction from 8 + 0 to 12 + 6 weeks' gestation. The majority (95%) of pregnancies had a fetal DNA fraction > 4%, which is generally the limit for accurate aneuploidy detection by NIPT. Across this early gestational time period, there was a weak inverse relationship (R2 = 0.186) between fetal DNA fraction and maternal weight. Conclusions NIPT is highly reliable and accurate when applied to maternal DNA samples collected from pregnant women in the first trimester between 8 + 0 and 12 + 6 weeks. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.